Cryomechanical Freezing. A Model for the Heat Transfer Process - Agnelli, Miriam Eliana (2001)
Cryomechanical freezing consists of a two-step process. During the first step, the foodstuff gets into contact with a cryogenic refrigerant for a very short period of time, during which a thin frozen crust is formed. Immediately afterwards, freezing is completed in a conventional cold air-blast freezer. In this work, the heat transfer process during cryomechanical freezing was modelled using the enthalpy formulation with a finite volume scheme. The results of the model were successfully compared with experimental data obtained in the literature for a model food (cylinders of gelatin) and for real foodstuffs (hamburgers, meatballs and strawberries) in a pilot prototype.